The Role of Demographic Characteristics and Spiritual Dimensions in Predicting Empathy: A Study in Muslim Pre-Service Teachers - Fitriyah, Fifi Khoirul; Hidayah, Nur; Muslihati, Muslihati; Hambali, Im; Ibad, Mursyidul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Although many studies have examined the relationship between spirituality and empathy, very few studies have focused on demographic and spiritual dimensions in influencing empathy for pre-service teachers. This study analyzes the effect of gender, age, and years of formal education on spirituality and empathy and analyzes the influence of the spiritual dimensions on empathy. This research is a cross-sectional study, with 319 Muslim pre-service teachers as respondents. The data collection technique used an online questionnaire adapted from the Spirituality Assessment Scale (SAS) and the Interpersonal Reactivity Index (IRI). The results show that age affects spirituality, while empathy is influenced by age and gender. One unanticipated finding was that years of formal education had no effect on either spirituality or empathy. The most important finding of this study is the higher the level of innerness, the more likely it is to have high empathy. This study's findings are useful as an assessment material and creating counseling designs to increase empathy for pre-service teachers. This is a part of forming the ideal profile of counselors in schools later. Integrating Islamic values ​​is also an essential alternative in counseling for Muslims.